MANAJEMEN ASUHAN KEBIDANAN ANTENATAL PADA NY "N" DENGAN ABORTUS INKOMPLIT DI RSUD SYEKH YUSUF KAB. GOWA TAHUN 2019 - Tenriani Wulandari,; Saleha, Sitti; Inayah Sari, Jelita (Jurnal Midwifery, 2022)
Introduction Incomplete abortion is the loss of some of the product of conceptiononof pregnancy, causing some of the fetal tissues are still deposited in the uterus such as decidua and placenta. During the process, the initial sign isthe bleeding in the basal decidua followed by the occurrence of necrosis in the surrounding tissue. Afterwards, a part if not all of the conception product would be detached. As it is considered to be a foreign object, the uterus would contract to expel it. At week 8 of gestation, all of the products of conception would be excluded because the choreal villi had not deeply penetrated the decidua. At weeks 8-14 of gestation, the choreal villi already deeply entered the decidua. Therefore, at this stage, some of the conception would come out and some would remain which causes the bleeding on the mother. Method This case study investigated the case of incomplete Abortion on Mrs. “N” at Public Regional Hospital of Syekh Yusuf in Gowa Regency. This study was conducted by employing 7- stages midwifery care approach suggested by Helen Varney and SOAP documentation procedure. The results of the case study conducted on Mrs. “N” indicated that the patient got an incomplete abortion case based on an anamnesis and physical examination taken. Mrs. "N", came to the regional hospital of Syekh Yusuf Gowa with the complaint of bleeding from her birth canal. The patient said that she had been bleeding since October 5, 2019 which stopped after wards. On October 30, 2019 at 6:00 a.m., there was blood as a result of her massage a couple of weeks before. The condition of the patients was considered to be weak, composmentis with the blood pressure of 110/70 mmHg. Her uterine fundal height was not palpable, and her ostium uteri externum and internum were closed. Based on the ultrasound examination with her residual tissue impression, uterine anteflexion, and FL (-), the patient was possibly diagnosed to get an incomplete abortion. Therefore, curettage was administered. On the first day after the curette, the patient’s condition improved. There was some bleeding and pain felt from the vagina, particularly from her lower abdomen. However, in general, the curettage was considered to be successful in which no obstacles were found during the implementation of the procedure. Conclusion After conducting an assessment and analysis based on the 7-stages of Varney and SOAP documentation procedure, it was apparent that the diagnosis given to Mrs “N” was the incomplete abortion case. Therefore, curettage was administered to the patient, and it had been succesfully conducted by the health workers in the hospital.